An ab initio study of some binary complexes containing methyl fluoride and difluoromethane: red-shifting and blue-shifting hydrogen bonds. (3rd July 2018) - Ramasami, Ponnadurai; Ford, Thomas A.
ABSTRACT: The properties of a number of hydrogen-bonded complexes of methyl fluoride and difluoromethane with a range of hydrides of the first two rows of the periodic table have been computed using ab initio molecular orbital theory. The aim of this work was to identify possible examples of blue-shifting hydrogen-bonded species analogous to those formed between fluoroform and ammonia, water, phosphine and hydrogen sulphide, reported earlier. The calculations were carried out using the Gaussian-09 program, at the second-order level of Møller–Plesset perturbation theory, and with the aug-cc-pVTZ basis sets of Dunning. The properties studied include the molecular structures, the hydrogen bond energies and the vibrational spectra. The results have been interpreted with the aid of natural bond orbital theory and the quantum theory of atoms in molecules. Abstract :